An Application Related to Logistics Social Responsibility Evaluation with DEMATEL and ELECTRE Methods - PEKER, İskender (Journal of Economics Bibliography, 2016)
Abstract. The issue of environment becomes one of the privileged areas determined in the framework of social responsibility when national and international ethical scandals are experienced in various sectors. Therefore, to analyze activities of logistics firms in the framework of social responsibility theme gains importance while evaluating the activities in terms of their environmental effects. In regard to this important aspect, the purpose of this study is determined as to specify and prioritize the criteria which logistics firms should take into account while performing their social responsibility activities then to select the logistics firm which has the highest level of social responsibility. In this manner, DEMATEL method is used for weighting the criteria and ELECTRE method is used for firm selection. Analysis results show that “breakdown of fleet composition” criteria is the most important logistics social responsibility criteria while C firm has the highest level of social responsibility. Keywords. Logistics, Social responsibility, Multi criteria decision making. JEL. M10, M11, M14.